Placing Users at the Center: Evaluating Exam Room Design for Improved User Experience. (October 2022) - Matić, Zorana; Oh, Yeinn; Lim, Lisa; Zimring, Craig
Objective: This article proposes a method for evaluating the design affordances of primary care exam rooms from the perspectives of users using functional scenario (FS) analysis. Goal: This study aims to develop quantifiable criteria and spatial metrics for evaluating how exam room design supports the needs of different users. These criteria and metrics can be used in the early stages of the design process to choose between alternatives. Background: The primary care exam room is an essential space in healthcare, as it is the first point of contact between the healthcare provider and the patient. However, there is a lack of rigorous evaluation metrics for exam room design that supports improved user experiences and better health outcomes. Method: A total of nine primary care exam rooms were analyzed using FS analysis. We identified three key user groups involved in the clinical examination process—providers, patients, and care partners—and translated their needs into FSs. We developed spatial metrics for each FS to quantify the extent to which the needs were spatially supported. Results: We developed 11 FSs in total: three from the providers', five from the patients', and three from the care partners' perspectives. The results revealed possible design strategies for improved user experiences. Conclusions: We quantitatively measured the affordance of primary care exam room design for multiple stakeholders. We expect that the criteria and metrics presented in this article will improve the understanding of different users' perspectives and provide new design guidance for improved user experiences.